PERFORMANCE E-GOVERNMENT UNTUK PENINGKATAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN INFRASTRUKTUR DI KABUPATEN SIDOARJO - Budi Guntoro, Totok Wahyu Abadi, Nunung Prajarto, dan (Jurnal Kawistara, 2014)
The Innovation of website by local governments can actually be used to improve public services and encouragecommunity participation in development.This study aims to analyze and explain (1) the performance ofe-government, (2) participation in infrastructure development, and (3) the influence of the performanceof e-government toward public participation in infrastructure development in Sidoarjo. The method usedis explanatory approach with a sample of 233 respondents as the users of the local government of Sidoarjo.Analyzing technique used is multiple regression and path analysis. The results showed that the performanceof e-government in Sidoarjo district that includes ease of use, usefulness, web interface, a complementaryrelationship, as well as public services is categorized as good at 68.81%. Public participation in infrastructuredevelopment is regarded as medium category, which is 57.12%. The most dominant community participationis information search, supervision; discussion or public consultation; partnership in the provision of funds,energy, and thought. The performance of e-government significantly influences the participation. Gender alsodirectly affects community participation and indirectly affects participation through the use of e-government.